2013
DOI: 10.1515/labmed-2013-0043
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry and drug-monitoring of natalizumab saturation of immune cells in multiple sclerosis1)

Abstract: Background: Natalizumab (Tysabri) is a blocking antibody specific to the α -4 integrin subunit and can be detected on the surface of immune cells by flow cytometry. We investigated if the determination of natalizumab saturation of immune cells has the potential to act as a biomarker for treatment effectiveness in multiple sclerosis (MS). Methods: Natalizumab saturation of immune cells from 11 patients was measured before the start of treatment and after 4, 8, and 12 weeks of natalizumab therapy on T cells (CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
2
3
0
4
Order By: Relevance
“…It is important to have a biomaker which is informative if the treatment can be effective. This study, and previous studies from our group, have shown that the natalizumab saturation level of immune cells can be such a biomarker [11,12] . We demonstrated the importance of regular 4-weekly infusion intervals by showing that patients experience strong fluctuations in their cellular natalizumab saturation levels in case of prolonged infusion intervals of 6 -8 weeks [12] .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…It is important to have a biomaker which is informative if the treatment can be effective. This study, and previous studies from our group, have shown that the natalizumab saturation level of immune cells can be such a biomarker [11,12] . We demonstrated the importance of regular 4-weekly infusion intervals by showing that patients experience strong fluctuations in their cellular natalizumab saturation levels in case of prolonged infusion intervals of 6 -8 weeks [12] .…”
Section: Discussionsupporting
confidence: 74%
“…This study, and previous studies from our group, have shown that the natalizumab saturation level of immune cells can be such a biomarker [11,12] . We demonstrated the importance of regular 4-weekly infusion intervals by showing that patients experience strong fluctuations in their cellular natalizumab saturation levels in case of prolonged infusion intervals of 6 -8 weeks [12] . Furthermore, we demonstrated in a patient with NAB that freshly infused natalizumab transiently neutralized NAB to the end that serum NAB were no longer detectable but natalizumab saturation levels of immune cells had recovered.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Andere Studien zeigten jedoch, dass der NatalizumabSättigungsgrad ein stabilerer Parameter ist als die CD49d-Expression, um Rückschlüsse auf den Therapieerfolg von Natalizumab ziehen zu können [11,12]. Der NatalizumabSättigungsgrad berechnet sich aus dem Vergleich von in vivo gebundenen Natalizumab und dem in vitro mit Natalizumab gesättigten Immunzellen.…”
Section: Introductionunclassified